Analisis Kesulitan Pembelajaran FPB dan KPK di Kelas 5 SDN Kampung Besar 2 Teluknaga - Nabilah, Nabilah; Unaenah, Een; Lestari, Linda; Nurvitasari, Nurvitasari (MASALIQ, 2022)
This study aims to explain the difficulties of grade 5 students at SDN Kampung Besar 2 Teluknaga in learning mathematics regarding FPB and KPK materials. And also the teacher's efforts in overcoming the difficulties of learning mathematics in the FPB and KPK materials. This study uses a descriptive research method with qualitative research with the research subject being a 5th grade teacher at SDN Kampung Besar 2 Teluknaga. The research instruments used were observation, interviews, and documentation. The results of the study revealed that grade 5 students of SDN Kampung Besar 2 Teluknaga studied FPB and KpK material by orienting students to contextual problems where in this problem students could explore and also with models or methods that were familiar with the student's own world. And most of the students already understand the material for FPB and KPK with the method given by the teacher. And there are only a few students who really don't understand the material, it's probably caused by 2 factors and it can still be evaluated by the teacher. And students also think that mathematics is a difficult, boring, rigid, and not fun learning and that is the wrong perception. there are 2 possible factors in the difficulties regarding FPB and KPK learning experienced by these students, namely: internal factors and external factors. Where the internal factors of the students themselves lack psycho-physical, namely the lack of capturing information explained by the teacher and external factors, namely the absence of encouragement to learn from parents so that students are not motivated in learning. And as educators should be able to convey material so that it is easily understood by students. So that students are also not easily bored and passive in learning. So the method or media used can attract students' attention and motivate student learning, especially on FPB and KPK materials in class 5 at SDN Kampung Besar 2 Teluknaga.